Nanofocused x-ray photon correlation spectroscopy - Berkowicz, Sharon; Perakis, Foivos (Stockholm University, 2022)
Supplementary datasets (from published figures) and example code.

Example notebook (example_notebook_data.ipynb) shows how to load and use the datasets.

Datasets:


- Scattering intensity for nanoparticles in water and in dmso-water solution at different sample positions as a function of momentum transfer q (Iq_values.dat).

- Intensity autocorrelation g2 functions for different momentum transfer q and corresponding fit parameters. One .dat file for each type of nanoparticle (NP) sample and measurement conditions, i.e. sample position along the nanofocused x-ray beam: g2_NPwater.dat (NP in water in the focal plane), g2_NPdmso_1.dat (NP in dmso-water in the focal plane), g2_NPdmso_2.dat (NP in dmso-water 1 mm out) , g2_NPdmso_3.dat (NP in dmso-water 2 mm out).



See link to github for analysis codes.
Keywords: Condensed matter physics not elsewhere classified; Condensed Matter Physics; Den kondenserade materiens fysik